Intermittent lead‐induced stress on antioxidant enzyme activity and subcellular distribution of Pb in Pogonatherum crinitum seedlings. (19th February 2019) - Hou, X.‐L.; Han, H.; Meng, F.‐R.; Cai, L.‐ P.; Liu, A.‐Q.
Abstract: Pogonatherum crinitum is a promising lead (Pb) hyperaccumulator due to its high Pb tolerance and accumulation ability. However, the mechanisms that support Pb accumulation and tolerance in P. crinitum are not yet clearly understood. An indoor hydroponic experiment was conducted by cultivating P. crinitum seedlings exposed to intermittent Pb stress for 60 days, divided into four stages (T1, T2, T3 and T4), with a 15‐day duration per stage. The following concentrations of Pb were used: 0, 500, 0, 500 mg·l −1 and 0, 1000, 0, 1000 mg·l −1 ). Antioxidant enzyme activity, Pb concentration and subcellular distribution of Pb were measured at each of the above stages. The results showed that superoxide dismutase (SOD) activity in shoots, and SOD, peroxidase (POD) and malondialdehyde (MDA) activity in shoots and roots significantly increased from T1 (no Pb stress) to T2 (Pb stress) in both 500 mg·l −1 and 1000 mg·l −1 treatments; however, no significant difference was noted between stages T3 (no Pb stress) and T4 (Pb stress). There was no obvious effect of Pb stress on catalase (CAT) activity in shoots and roots among different stages. The Pb concentration in shoots was up to 5090.90 mg·kg −1 and 7573.57 mg·kg −1, and the bioconcentration factor (BFC) was 10.18 and 7.57 for the 500 mg·l −1 and 1000 mg·l −1 treatments, respectively, which confirmed the Pb hyperaccumulator characteristics of P. crinitum . For plants under Pb stress, most of the Pb was fixed in the cell walls, with a smaller amount in leaves and root vacuoles. Both SOD and POD scavenging of reactive oxygen radicals and fixing and compartmentalisation of Pb in the cell wall might play important roles in detoxification of P. crinitum seedlings in response to Pb stress. There was no phased response of P. crinitum to intermittent Pb stress and the physiological response to Pb stress may be contiguous.